Smart tourism como objeto cultural da indústria criativa: a potencialização das novas mídias na cultura da convergência - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This research sought proposes to analyze how smart tourism initiatives that use the internet of things are being characterized as cultural objects of the creative industry, based on trends in the culture of convergence. In that regard, the relationships between communication, cyberculture, convergence, creative industry and smart tourism are investigated, as well as new media, probable ways of the internet of things and the optimization of smart tourism as a cultural object of the creative industries. The problem of this research was guide by the questioning of how smart tourism is configured as a cultural object of the creative industry in the context of the culture of convergence, considering the traditional classifications of the subgroup new media. For this purpose, the case of smart tourism of the startup Smart Tour Brasil, from Santa Catarina, is analyzed, as well as its strategies regarding the city of Florianópolis/SC, which had the most intensive use of smart tourism from the use of the internet of Things (IoT), advised by the startup. For this purpose, we used the case study, based on Yin (2015), with triangulation of simple exploratory observation techniques (GIL, 2008), in-depth semi open interview (DUARTE; BARROS, 2010) and systematic exploratory observation ( Gil, 2008). From all that has been observed, it is concluded that smart tourism is a new cultural object of the creative industry, as well as, it has the potential to create much more than creative digital content, that is, it creates interaction models. Finally, all smart tourism practices are permeated by digital.
Keywords: Turismo; Mídia digital; Inovações tecnológicas; Internet das coisas; Cultura e turismo; Indústria cultural; Tourism; Digital media; CNPQ::CIENCIAS SOCIAIS APLICADAS